2021
DOI: 10.3390/cancers13235994
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Therapy in HR+ HER2− Metastatic Breast Cancer: Current Clinical Trials and Their Implications for CDK4/6 Inhibitor Therapy and beyond Treatment Options

Abstract: A metastatic state of breast cancer (MBC) affects hundreds of thousands of women worldwide. In hormone receptor-positive (HR+)/human epidermal growth factor receptor 2-negative (HER2−) MBC, cyclin-dependent kinase (CDK)4/6 inhibitors can improve the progression-free survival (PFS), as well as the overall survival (OS), in selected patients and have been established as first- and second-line therapies. However, as MBC remains uncurable, resistance to CDK4/6 inhibitors occurs and requires alternative treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…Our study only suggested the tendency of CDK4/6 inhibitor-containing treatment regimens toward better OS from the view of SUCRA values. Currently, there are still challenges in differentiating the population that can acquire OS benefit from CDK4/6 inhibitors due to the profound heterogeneity of patients ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study only suggested the tendency of CDK4/6 inhibitor-containing treatment regimens toward better OS from the view of SUCRA values. Currently, there are still challenges in differentiating the population that can acquire OS benefit from CDK4/6 inhibitors due to the profound heterogeneity of patients ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“… 396 Since 2015, three CDK4/6 inhibitors, palbociclib, ribociclib, and abemaciclib have been approved for HR‐positive/HER2‐negative breast cancer in various settings and combination regimens. 397 , 398 The addition of the CDK4/6 inhibitors palbociclib, ribociclib, and abemaciclib to an aromatase inhibitor were studied in postmenopausal HR‐positive/HER2‐negative advanced breast cancer in the first‐line setting in PALOMA‐2, MONALEESA‐2, and MONARCH‐3 trials, respectively. The three combination regimens nearly doubled the duration of median PFS and improved ORR compared with the single‐use of an aromatase inhibitor, with or without prolonged OS.…”
Section: Selective Small Molecule Kinase Inhibitorsmentioning
confidence: 99%
“…Fortunately, neutropenia and leukopenia are relatively easy to manage in clinic. 398 In 2021, the newest CDK4/CDK6 inhibitor, trilaciclib, was permitted for patients with SCLC indicated to prevent chemotherapy‐induced myelosuppression. 407 SCLC is an ideal disease model to assess the myeloprotective effect of trilaciclib.…”
Section: Selective Small Molecule Kinase Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations